2007
DOI: 10.1097/ajp.0b013e3180330dc5
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric History and Psychologic Adjustment as Risk Factors for Aberrant Drug-related Behavior Among Patients With Chronic Pain

Abstract: Psychiatric factors, such as a history of mood disorder, psychologic problems, and psychosocial stressors, may place patients at risk for misuse of prescription opioids. Future studies to elucidate the risk of medication misuse and aberrant drug behavior among this patient population are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
154
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(171 citation statements)
references
References 37 publications
11
154
5
Order By: Relevance
“…15,[20][21][22] These conditions were identified from ICD-9-CM coded diagnoses from inpatient and outpatient visits (available online). Drug and alcohol use disorders were defined by an ICD-9-CM code for abuse, dependence, poisoning, withdrawal, or psychosis within our study timeframe.…”
Section: Classification Of Risk Factors For Opioid Misusementioning
confidence: 99%
See 1 more Smart Citation
“…15,[20][21][22] These conditions were identified from ICD-9-CM coded diagnoses from inpatient and outpatient visits (available online). Drug and alcohol use disorders were defined by an ICD-9-CM code for abuse, dependence, poisoning, withdrawal, or psychosis within our study timeframe.…”
Section: Classification Of Risk Factors For Opioid Misusementioning
confidence: 99%
“…19 Patients with a history of drug abuse or dependence have an increased risk of prescription opioid abuse or dependence 15 and up to six times greater risk of aberrant medication-related behaviors such as prescription forgery or obtaining opioids from lay persons. 14,17,20 Alcohol use disorders, 14,21 tobacco use, 21 and mental health disorders 15,[20][21][22] are also associated with an increased risk for opioid misuse.…”
Section: Introductionmentioning
confidence: 99%
“…Misuse is defined as the use of any psychoactive substance in a way other than that for which it has been indicated or prescribed (Wasan et al, 2007). In practical terms, opioid misuse means: inadequate pain management, ineffective treatment, excessive focus on the drug and its effects which does not allow the patient to use other strategies efficaciously to cope with the pain, and finally, worsening of quality of life and altered social, working and psychological functioning.…”
Section: Breakthrough Painmentioning
confidence: 99%
“…A significant correlation has been found between chronic pain, mood disorders and aberrant drug use: patients with chronic pain report higher levels of anxiety and depression than patients with other medical conditions, and the incidence of mood disorders has been shown to be higher in patients at high risk of opioid misuse or dependence (Bair et al, 2003;Dersh et al, 2002;Fishbain, 1999 Using logistic regression, the authors showed that panic attacks, high trait anxiety and the presence of a personality disorder are able to explain the 38% variance in potential abuse of prescribed opioids. To investigate the role of psychological adjustment and psychiatric symptoms in aberrant drug behaviours in pain patients, Wasan et al (2007) divided the 228 patients enrolled into high-psychiatric and low-psychiatric morbidity, based on the responses to the psychiatric subscale of the Prescription Drug Use Questionnaire (PDUQ; Compton et al, 2008;see § 2.4.). Patients with high psychiatric comorbidity were significantly younger, with a longer mean opioid assumption time (p<0.05); altered urine toxicology screening results were also more frequent among these patients (p<0.01), and they often displayed aberrant drug-related behaviours.…”
Section: Risk Factors For Opioid Abusementioning
confidence: 99%
“…Another polymorphism of pre and pro-encephalin (PENK) and of melanocortin type 2 receptor (MC2R) is associated to opioid addiction in several studies 58 . The use of tests to identify the potential for opioid addiction and abuse should be according to risk stratification: 1) low risk, no history of substance abuse or psychiatric comorbidity (DSM4); 2) medium risk, history of substance abuse or of psychiatric comorbidities (DSM4); 3) high risk, history of dependence and aberrant behavior (theft of prescription, falsification of prescription, injectable use of oral substances, alcohol abuse, aggressively requesting prescription, multiple entries in emergency units, loss of job, family and social life position) [59][60][61] . The chance of developing opioid abuse increases as individuals present more than one risk factor and positive toxicological urine tests are more frequent 62 .…”
Section: Abuse and Addictionmentioning
confidence: 99%